Penggunaan Strategi Pembelajaran True or False Dalam Mata Pelajaran SKI Untuk Meningkatkan Minat Belajar Siswa Kelas Viii 6 di MTSN 2 Pasaman Barat - Karim, Hamdi Abdul; Mirta, Sapna; Marlina, Inang (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In Indonesia, the main national development initiative is education. This type of research uses a qualitative descriptive research methodology. From the results of research conducted by researchers and researchers, it shows that students' interest in learning has increased after using the True or False strategy. The proof is every time they learn to ski, which was boring for some students at first, but now all students are enthusiastic and more ready to learn, because of the true or false strategy.True or false is able to overcome student boredom in learning, especially in ski learning which tends to use the lecture method so that it makes students bored and sleepy. However, here the lecture method is still used but in collaboration with a true or false learning strategy. Then the researcher conducted an interview with one of the students in Class VIII 6. He said that learning to ski was really boring, especially during the last learning period. However, when using the true or false strategy the feeling of boredom disappears, because here we are required to work, think, discuss and choose, not just listen to the teacher explain, so we feel bored, sleepy and leave the classroom so learning is not effective.